An analysis of innovation competitiveness of China through patent analysis - Lei, Xiao-Ping; Chen, Dar-Zen; Huang, Mu-Hsuang; Zhao, Zhi-Yun; Zhang, Xu; Zheng, Jia; Zhao, Yun-Hua; Zhang, Ze-Yu; Liu, Run-Sheng (Malaysian Journal of Library and Information Science, 2017)
Lei, X. P., Chen, D. Z., Huang, M. H., Zhao, Z. Y., Zhang, X., Zheng, J., ... & Liu, R. S. (2012). An analysis of innovation competitiveness of China through patent analysis. Malaysian Journal of Library & Information Science, Vol.17, no. 2: 17-32. This article assesses the innovation competition characteristics in China through patent analysis. The Chinese patents in US Patent and Trademark Office (USPTO) database from 2004 to 2008 are used for analysis. The findings suggest that the innovation competitiveness of China has increased in recent years. The absolute number of patents has shown the trend of rapid growth, but the share of utility patents is much lower than the global share. Based on analysis of technology fields, two main high innovation technology fields of China are the Electrical and Electronic machinery (E&E) and Computer and Communication (C&C) fields. The main international technology cooperation partner in these two fields is Taiwan. Moreover, Chinese patent output in the US is concentrated on a few large enterprises, and the patent proportions of the top 5, 15 and 30 assignees have increased each year. The top 5 patent assignees demonstrate strong innovation competitiveness in C&C and E&E fields. Among the large assignees are Hong Fu Jin Precision in both E&E and C&C fields, and Fu Zhun Precision and Huawei Technologies in E&E and C&C field respectively